Model Pengembangan Kompetensi Pemandu Wisata Budaya di Rumah Adat Karo Selayang dalam Menghadapi Kebutuhan Wisata Edukasi - Alhafiizh, Rahmat; Wahyuda, Tri; Irmayana , Irmayana; Harahap, Donna Sapitri; Mudrika, Annisa Dea; Sirait, Ilham Adithiya; Windari, Sri (Dampeng: Journal of Art, Heritage and Culture, 2025)
This study focuses on the urgency of developing the competence of cultural tour guides at the Karo Traditional House Garista, located in Medan Selayang, in response to the increasing demand for the educational tourism sector. Garista, an authentic Siwaluh Jabu (eight-family house) that was relocated and preserved, serves as a knowledge center rich in philosophical value and the uniqueness of nail-less architecture, making it a vital destination for students, university students, and researchers. Therefore, the guides at this site are required to possess competence beyond general standards, specifically the ability to perform educational interpretation rather than mere description, ensuring that the essence of Karo culture is conveyed with depth and substance. This research aims to formulate an ideal model for competence development, which includes identifying existing guide competency gaps, determining the key elements required (knowledge, skills, and attitude), and designing a structured training model. Methodologically, the study will utilize a qualitative descriptive approach with data collection techniques involving triangulation, including in-depth interviews with managers, guides, and local cultural experts, participatory observation of the guiding process, and document analysis. The expected outcome is a Guide Competency Development Model oriented towards strengthening cultural narratives that can significantly enhance the educational tourism experience, while simultaneously contributing to the preservation efforts of the Karo heritage in an urban environment.  [Penelitian ini memfokuskan pada urgensi pengembangan kompetensi pemandu wisata budaya di Rumah Adat Karo Garista, yang berlokasi di Medan Selayang, sebagai respons terhadap meningkatnya permintaan sektor wisata edukasi. Garista, sebuah Siwaluh Jabu (rumah delapan keluarga) otentik yang dipindahkan dan dilestarikan, berfungsi sebagai pusat pengetahuan yang kaya akan nilai filosofis dan keunikan arsitektur tanpa paku, menjadikannya destinasi vital bagi pelajar, mahasiswa, dan peneliti. Oleh karena itu, pemandu di situs ini dituntut untuk memiliki kompetensi di atas standar umum, yaitu kemampuan untuk melakukan interpretasi edukatif alih-alih sekadar deskripsi, agar esensi budaya Karo dapat tersampaikan secara mendalam dan berbobot. Penelitian ini bertujuan untuk merumuskan model pengembangan kompetensi yang ideal, mencakup identifikasi kesenjangan kompetensi pemandu yang ada, penentuan elemen-elemen kunci yang dibutuhkan (pengetahuan, keterampilan, dan sikap), dan perancangan model pelatihan yang terstruktur. Secara metodologis, penelitian ini akan menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data triangulasi meliputi wawancara mendalam dengan pengelola, pemandu, dan budayawan lokal, observasi partisipatif terhadap proses guiding, serta analisis dokumen. Hasil yang diharapkan adalah Model Pengembangan Kompetensi Pemandu yang berorientasi pada penguatan narasi budaya dan mampu meningkatkan pengalaman wisata edukasi secara signifikan, sekaligus berkontribusi pada upaya pelestarian warisan Karo di wilayah urban.]